Komunikasi Kebencanaan: Suatu Strategi Dalam Membangun Masyarakat Sadar Bencana Pada BPBD Kota Mataram - Baiq Vira Safitri; Shinta Desiyana Fajarica; Yulanda Trisula; Novita Maulida; Gemuh Surya Wahyudi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
A disaster is an event that threatens and disrupts people's lives and livelihoods which are caused, both by natural and / or non-natural factors as well as human factors, resulting in human casualties, environmental damage, property loss and psychological impacts. According to Law Number 24 of 2007 concerning Disaster Management, disasters are classified into three parts; natural disasters, non-natural disasters and social disasters. The impact of disasters, especially natural disasters, varies from the moment of occurrence to post-disaster. Referring to the series of earthquake events in Lombok on 29 July 2018 (M6.4), 5 August 2018 (M7.0) and 19 August 2018 (M6.9), until 1 September 2018 has claimed 564 victims and suffered losses with the total rough count reached IDR 12.15 trillion. The impact of the earthquake is a lesson for the government and related agencies, in this case the Mataram City BPBD to better prepare disaster management strategies in a mature and planned manner. This study aims to determine the disaster communication strategy of the Mataram City BPBD in building a disaster-aware Mataram community using qualitative methods. The results of the research also show, among others: (1) Determination of communicators / community leaders as a credible source; (2) Selection of messages that are easy to understand; (3) Selection of disaster reporting media; (4) Mapping communication barriers in building disaster-aware communities.